Improvement of the power conversion efficiency and long term stability of polymer solar cells by incorporation of amphiphilic Nafion doped PEDOT-PSS as a hole extraction layer1. Issue 36 (28th September 2015) - Hou, Xuliang; Li, Qiuxiang; Cheng, Tai; Yu, Lu; Wang, Fuzhi; Lin, Jun; Dai, Songyuan; Li, Yongfang; Tan, Zhan'ao
<x xml:space="preserve">Abstract</x> An effective method to enhance the conductivity and stability of PEDOT-PSS by doping with an amphiphilic perfluorosulfonic copolymer is reported.